Small bowel stenosis after blunt abdominal trauma: a case report - Kazushi Hara; Manabu Yamamoto; Teruhisa Sakamoto; Ken Sugezawa; Chihiro Uejima; Akimitsu Tanio; Yoichiro Tada; Takehiko Hanaki; Kozo Miyatani; Joji Watanabe; Kyoichi Kihara; Naruo Tokuyasu; et al. (Surgical Case Reports)
Abstract Background Small bowel stenosis after blunt abdominal trauma is relatively rare, and progression from trauma to bowel stenosis might sometimes be delayed. Herein, we report the case of a patient who was diagnosed with small bowel stenosis relatively early and received laparoscopic surgery. Case presentation An 18-year-old Japanese male was in a traffic accident and was urgently transported to our hospital. On arrival, he was admitted with right kidney and right adrenal injury and abdominal aortic aneurysm. On hospital day 13, he vomited during conservative treatment without surgery, and computed tomography revealed small bowel stenosis and dilatation of the oral-side small bowel. No improvement with the ileus tube occurred, and he received laparoscopic surgery on hospital day 21. Briefly, the abdominal cavity was observed with a laparoscope. The mesentery was congested, scarring around the stenotic small bowel regions was present, and three stenotic regions were observed 40–50 cm from the Treitz ligament. The patient received partial resection and anastomosis of the small bowel. The postoperative course was stable, and he was discharged on postoperative day eight. Conclusions Most cases of bowel stenosis after abdominal trauma are irreversible and usually require surgical treatment. Therefore, small bowel stenosis should be considered in patients with abdominal symptoms after blunt abdominal trauma.